2021
DOI: 10.4103/jrms.jrms_35_21
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and tumor necrosis factor-α levels in tear film of Keratoconus patients

Abstract: Background: It is hypothesized that increased inflammatory markers in keratoconus (KC) may be one of the causes of corneal damage. The aim of our study was to the measurement of tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL)-6 in tear of patients with KC and investigate their relationship with the severity of KC. Materials and Methods: The current study was performed on KC patients and healthy controls with a case-control setting. Tear level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Despite some publications with different results [19,29], in our study, when comparing the concentrations of the cytokines we examined in the control group and the group with KC, we found that the levels of all the cytokines we investigated were significantly higher in the control group than in the study group. This may be a result of the tests used to detect the levels of these factors [50]. Our study was conducted based on results from flow cytometry, which is an extremely specialised technique used to differentiate cell populations based on morphological features and antigenic composition.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some publications with different results [19,29], in our study, when comparing the concentrations of the cytokines we examined in the control group and the group with KC, we found that the levels of all the cytokines we investigated were significantly higher in the control group than in the study group. This may be a result of the tests used to detect the levels of these factors [50]. Our study was conducted based on results from flow cytometry, which is an extremely specialised technique used to differentiate cell populations based on morphological features and antigenic composition.…”
Section: Discussionmentioning
confidence: 99%